Contextualized high-speed running and sprinting during English Premier League match-play with reference to possession, positional demands and opponent ranking - Morgans, Ryland (2025)
This study aimed to compare high-speed running (HSR) and sprint distances (SD) when in- (IP) and out-of-possession (OP) during official English Premier League (EPL) match-play over three consecutive seasons considering playing position, match location and opponent ranking. Match data from 31 male professional soccer players was obtained via an optical tracking system. Results showed that during the IP phase, playing position emerged as the only significant predictor for both HSRIP and SDIP. Wingers showed the highest HSRIP compared to centre-backs who exhibited the lowest values (p < 0.001, ES = 4.19). Similar data were found for SDIP (p < 0.001, ES = 3.30). HSROP was significantly affected by both ranking difference (β = -0.039, p = 0.001) and match location (β = 0.369, p = 0.001). HSROP decreases as the ranking difference increases and tends to be higher during away matches (p = 0.001, ES = 0.24). SDOP was affected by both ranking difference (β = -0.023, p = 0.001) and match location (β = 0.166, p = 0.001) and decreased as the ranking difference increased. SDOP was also higher during away matches (p = 0.001, ES = 0.23). Additionally, a significant interaction was found between playing position and ranking difference (β = 0.005, p = 0.010). Lower ranking differences correspond to higher SDOP values. In conclusion, these findings highlight that by applying these IP and OP insights into practical coaching strategies, teams can potentially enhance individual physical performance and adaptability across different match situations and seasons.